The comorbidity between depression and diabetes (2013)
"Comorbidity of depression and diabetes is common, and each disorder has a negative impact on the outcome of the other. The direction of causality is not certain as each disorder seems to act as both a risk factor and consequence for the other in longitudinal studies. This bidirectional association is possibly mediated by shared environmental and genetic risk factors. Comorbid depression is associated with reduced adherence to medication and self-care management, poor glycaemic control, increased health care utilization, increased costs and elevated risk of complications, as well as mortality in patients with diabetes. Psychological and pharmacological interventions are shown to be effective in improving depression symptoms; however, collaborative care programs that simultaneously manage both disorders seem to be most effective in improving diabetes-related outcomes."